Metabolic and cardiovascular effects of early insulin glargin prescription: based on data from ORIGIN study - Elena Valer'evna Biryukova; Alexander Sergeevich Ametov; Mikhail Borisovich Antsiferov; Alsu Gafurovna Zalevskaya; Galina Afanas'evna Mel'nichenko; Ashot Musaelovich Mkrtumyan; Marina Vladimirovna Shestakova (Сахарный диабет)
We discuss results of ORIGIN, a multicenter parallel groups study for efficiency assessment of insulin glargin against polyunsaturatedomega-3 fatty acids or placebo regarding cardiovascular and/or mortality risk reduction in patients with impaired fasting glycemia,impaired glucose tolerance or type 2 diabetes mellitus (T2DM) on its early stage and high risk for cardiovascular events. 12 537 patientstook part in this study; 6 264 were randomized in insulin glargin group, where dosage was adjusted for complete compensationof fasting glycemia (5.3 mmol/l was set as a therapeutic goal). After treatment with glargin therapeutic goal was achieved and furthermaintained for 6.2 years of follow-up. Compensation of fasting glycemia did not affect the outcome of cardiovascular diseases in patientswith early stages of dysglycemia according to primary endpoints. It was not associated with increase in general morbidity and inrisk of hypoglycemic events. Treatment with insulin glargin delayed progression from prediabetes to clinical onset for 28% (OR 0.72,CI 95% 0.58-0.91; p = 0,006), while lowering incidence of DM. Longtime treatment with insulin glargin does not increase incidenceof malignant tumors of different localization, including patients with prediabetes. Due to results of ORIGIN, insulin glargin (Lantus?)has become the most studied human insulin analogue to date.